Public-private partnership as a mechanism for improving cardiological assistance to the population at the regional level - A. V. Ivanyuk (Kazimierz Wielki University, 2020)
Objective: to substantiate the feasibility of forming a modern regional center for cardiology and cardiac surgery predicated on the basis of public-private partnership (PPP) mechanisms. Materials and methods. The research is performed with the use of the method of system approach and analysis, sociological and statistical methods are used as well. The scientific works of specialists in the field of health care and management, regulatory documents on the problem and the results of our own sociological researches were used as informational base for its implementation. Results. According to the analysis of resource provision of the cardiac service in Kyiv region, as well as a sociological survey of 829 patients with circulatory system diseases who applied to regional outpatient clinics, and 352 cardiologists from all regions of Ukraine survey, a comprehensive description of the conditions, problems and ways of improvement of cardiac care rendering to rural population was obtained. It is shown that a promising direction of development of cardiac care regional system is the formation of a new organizational model of the regional center for cardiology and cardiac surgery predicated on PPP principles. The article presents the legal framework for the use of PPP mechanisms, reveals the prospects and benefits of forming a model of a regional center for cardiology and cardiac surgery principled on PPP, identifies external and internal conditions for the model development, outlines the necessary practical measures for its implementation. Conclusions. The materials presented in the article prove that a promising direction of regional level cardiac care improvement is the formation of a new organizational model of the regional center for cardiology and cardiac surgery predicated on the principles of PPP.